Evaluation of Tranexamic Acid Effect on Consequences of Upper Gastrointestinal Bleeding in Patients Referring to the Emergency Department; a Randomized Clinical Trial - Morteza Talebi doluee; Sayyed Majid Sadrzadeh; Elnaz Vafadar-Moradi; Hamid Zamani moghadam; Sanaz Javdani (Patient Safety and Quality Improvement Journal, 2020)
Introduction: Upper gastrointestinal bleeding is one of the major and emergent causes of mortality and morbidity around the world. The tranexamic acid has been raised since years ago as a therapeutic intervention. Therefore, prize of exact and timely treatment of upper gastrointestinal bleeding, the present study aimed to evaluate the effects of systemic tranexamic acid on the possible consequences of upper gastrointestinal bleeding such as need for blood transfusion, admission in intensive care unit (ICU), surgery to control bleeding or eventually short-term mortality. Materials and Methods: This double-blind randomized clinical trial included 88 patients with upper gastrointestinal bleeding in a referral academic gastrointestinal center. Patients with symptoms of upper gastrointestinal bleeding referred to the emergency department were randomly divided into two groups: intervention group (n=45) who treated with tranexamic acid in addition to receive standard therapy for upper gastrointestinal bleeding, and control group (n=43) treated with standard therapy for upper gastrointestinal bleeding and placebo (distilled water). Results: Administration of tranexamic acid along with the standard therapy for upper gastrointestinal bleeding in the intervention group caused reduction in mortality and recurrent bleeding compared to the control group. There is no difference between two groups in need for surgery, hemotransfusion and ICU admission. Conclusion: Due to the beneficial effects of tranexamic acid administration on reducing mortality and bleeding recurrence in patients with upper gastrointestinal bleeding, added this drug to the standard therapy may have a favorable potential for upper gastrointestinal bleeding.